Expressão do gene vlxc no tegumento de sementes de soja - Borges, Carolina Terra (2013)
Soybean seed quality is high related with crop production. Seed coat has the function of maintaining this quality, since acts as a modulator of the interactions between the internal and external environment of the seed, controls gas exchange and water to the environment and regulates germination by interfering with the mechanisms dormancy. In soybean seed husk is present lipoxygenase VLXC, which is involved in the temporary storage of nitrogen. Given the above, the objective of this study was to evaluate the expression of the gene coding for the protein VLXC on the tegument of four soybean genotypes at different times of collection after anthesis. The experiment was conducted in greenhouse Station Lowlands of Embrapa Clima Temperado and Laboratório de biotecnologia de sementes (UFPel / FAEM) in the city of Capão do Leão - RS, in a completely randomized design with three replications, and treatments arranged in a factorial model. We used four contrasting genotypes, two cultivars of yellow coat (COODETEC 202 and BMX Potência RR) and two genotypes of black coat (Tegumento Preto and IAC). Samples were collected along the integuments of developing soybean seed corresponding to periods of 25, 30, 35, 40, 45, 50 and 55 days after anthesis. Proceeded to RNA extraction of tegument, followed by obtaining the cDNA for further analysis of qRT-PCR (polymerase chain reaction of reverse transcription real-time), to quantify the relative accumulation of gene transcripts VLX-C. The level accumulation of gene transcripts VLXC cultivar CD 202 has been raised most of the times, followed by a low expression evaluated last time that corresponds with the time it was made harvesting soybeans. The strain TP and the IAC and BMX Potência RR did not show the same behavior of the cultivar CD 202, due to low accumulation of gene transcripts VLXC in all periods. The results indicate that the relative accumulation of gene transcripts VLXC in the seed coat of soybeans differs between both periods evaluated, as well as between genotypes.